Center and Periphery, Interchangeable Poles: The Transculturation of the Brazilian in Anthropophagy and Bossa Nova - García Domínguez, Liliana (2025)
This paper aims to describe the transculturation processes of two pivotal moments in Brazilian art: Anthropophagy and bossa nova, both of which took place during the 20th century. Each, in its own way, was dynamic and disruptive, marking a turning point not only for Brazil but also for Latin America. As case studies, the analysis focuses on singer Carmen Miranda (in relation to Anthropophagy) and the musical productions of bossa nova. Carmen Miranda, “devoured” by the U.S. film industry, opened up that market to Latin American culture. Bossa Nova, on the other hand, represents the fusion of an entirely native rhythm with jazz—an exchange in which center and periphery merge and balance each other. Both moments were profoundly significant in the internationalization and introjection of Brazil and its culture into the Western world.